The current-voltage characteristics and inhomogeneous-barrier analysis of ddq/p-type Si/Al diode with interfacial layer - Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2007)
The current-voltage characteristics and inhomogeneous-barrier analysis of ddq/p-type Si/Al diode with interfacial layer have been investigated by current voltage measurements. The device behaves like an Schottky contact at low voltages. The obtained ideality factor n value is higher than unit. The current voltage characteristics of the diode show a nonideal behavior. This behavior arises from the series resistance and the presence of an interfacial layer formed during the surface preparation. The electronic parameters such as barrier height, ideality factor and series resistance of the device were determined using Cheung's method. The effect of the series resistance for the device was not ignored and the obtained values are lower than the equivalent values obtained previously without considering effect of the presence of interfacial layer. A decrease in OB and an increase in the ideality factor with decreasing temperature were observed and this case was explained on the basis of a thermoionic mechanism with Gaussian distribution. The obtained standard deviation, which is a measure of the barrier homogeneity, indicates the presence of the interface inhomogeneities. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Schottky diode; interfacial state density; series resistance